The Impact of Chronic Low-Back Pain on Quality of Life among Samples of Iraqi Patients: A Cross-Sectional Study - Nadia Ayad Mohammed Jawad; Mohammad Hadi Alosami; Zainab Fadhil Mahdi (Medical Journal of Babylon)
Background: The term “chronic pain” refers to discomfort that lasts longer than 3–6 months. Particularly in industrialized nations, low-back pain (LBP) and its accompanying limitations are becoming a rising public health concern. Disability is the inability to do an activity in a way that is appropriate for a human being or within their normal range. Objectives: The aim of this study was to examine the relationship between sociodemographic characteristics and pain severity and quality of life in chronic LBP (CLBP) patients from Iraq. Materials and Methods: The study was carried out between September 2020 and January 2021, involving 100 participants conveniently selected in the rheumatology unit at Baghdad Teaching Hospital/Medical City, Iraq. Data were collected using a questionnaire that consisted of the sociodemographic variables, the short form 36 score (SF-36), and the numerical pain score. The Statistical Package for Social Sciences was used for the statistical analysis. Results: In the study, there were 100 patients with persistent LBP, ranging in age from 17 to 58, with a mean (standard deviation [SD]) age of 45.54 (11.36) years. About 54% of them were female. Approximately 72% were married, and the highest percentage (40%) had a secondary educational level. The individuals under study had a mean body mass index (BMI) of 28.61 kg/m2. Nearly 12% of them were current smokers, and 46.0% were housewives. A higher mean Numerical Pain Score was reported among current smokers (P = 0.016). A nonsignificant difference in numerical pain score has been noted in relation to gender, age, marital status, occupation, BMI, and educational level (P values of 0.876, 0.06, 0.392, 0.307, 0.139, and 0.664, respectively). This study also revealed a low total score for quality of life among participants with increasing age, retired or not working, and widowed patients. Conclusion: Participants’ quality of life is significantly impacted by CLBP. On both the total level of quality of life and the mental area, it has a very adverse effect.